Bibliometric Study of CSIR- Institute of Himalayan Bioresource Technology (CSIR-IHBT) during 1990 – 2019” published in SRELS Journal of Information Management volume 57 (6) December 2020 pages 309-318 - Garg, K. C.; Kumar, S.; Kinwar, Deobardhan (Journal of Information and Knowledge, 2021)
No Abstract.